Xie's Chinese veterinary herbology - Preast, Vanessa; Xie, Huisheng (Wiley-Blackwell, 2010)
"Chinese Herbal Medicine (CHM) has been practiced for more than 4,000 years, and along with acupuncture is an important component of Traditional Chinese Veterinary Medicine. Veterinarians are increasingly using these treatment methods in a clinical setting, Chinese Veterinary Herbology will serve as a clear, practical guide to the theory and application of CHM into established veterinary practices. Chinese Veterinary Herbology will be divided into three parts. Part I will address herbal materia medica used in treating various disorders and diseases. Part II will provide 400 herbal formulas used in treating large and small animals. Part III will discuss the clinical application of herbal treatments. Within these sections the authors will also discuss the history of each herb, the basis of formulation of herbal recipes, energetic actions, indications, and contraindications of each formula, dosage requirements for both large and small animals and information on clinical and pharmacological studies performed with herbal treatments. Chinese Veterinary Herbology will serve as an invaluable reference and guide to all veterinarians looking to expand their treatment options"--Provided by publisher